Pandangan Yohanes Calvin Tentang Hubungan Gereja dan Politik serta Relevansinya Bagi Jemaat - Elungan, Novallick; Tamaweol, Roy Dekky (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This article discusses the relationship between church and politics through the views of John Calvin. This view emerged during Calvin's reformation of Geneva in 1536 and upon his return from Strasbourg to Geneva in 1541. The new life of the people of Geneva apart from the Roman Catholic Church and the Duke of Savoy required Calvin to organise Geneva's church government system. According to Calvin, church and politics are institutions established by God as external means. Calvin emphasised the separation between Church and Politics because both have different tasks, but they complement each other. In essence, Calvin holds the view that both church and politics are means established by God or what Calvin calls ‘God's representatives’ to regulate human behaviour in accordance with His will.